Poly(benzo[2, 1-b:3, 4-b′]dithiophene-alt-isoindigo): a low bandgap polymer showing a high open circuit voltage in polymer solar cells. Issue 1 (2nd December 2014) - Wan, Meixiu; Zhu, Hongbing; Liu, Juan; Huo, Lijun
Abstract : A novel polymer of PBDP-IID was synthesized and its HOMO descends to −5.44 eV. Bulk heterojunction solar cells made from PBDP-IID exhibited a high V oc of 0.95 V, which shows the highest value among the PSCs based on the narrow bandgap polymer donors with E g < 1.6 eV. Abstract : A novel optical band gap of 1.57 eV isoindigo (IID)-containing polymer of PBDP-IID was synthesized and the HOMO of the polymer descends to −5.44 eV due to strong electron-deficient isoindigo unit. Bulk heterojunction solar cells made from PBDP-IID exhibited a high V oc of 0.95 V, which shows the highest value among the PSCs based on the narrow bandgap polymer donors with E g < 1.6 eV.